Un projet participatif sur la réduction de la pollution atmosphérique dans quatre pays de l’Afrique de l’Ouest : quel rôle pour les femmes ? - Saint-Charles, Johanne; Yates, Stéphanie; Kêdoté, Nonvignon Marius (Recherches participatives et équité en santé, 2022)
C echapitreportesurlesdéfisd’uneapprocheparticipativeintégrant une perspective d’équité de genre rencontrés dans le cadre d’un programme de recherche-intervention sur la pollution urbaine en Afrique de l’Ouest, programme intitulé « Chaire écosanté sur la pollution urbaine de l’air et les maladies respiratoires1 ». Conçu et dirigé par des chercheurs et chercheuses de quatre pays africains (Bénin, Burkina Faso, Côte d’Ivoire et Sénégal), ce programme regroupait des équipes derecherchedechacundespays(équipes-pays)etquelquescollèguesde«paysdunord»,dontleCanada(Québec).IlaétéfinancéparleCentre de recherches pour le développement international du Canada. Outre des objectifs de recherche et de formation, la Chaire comportait un volet nommé Air-Sain qui visait à sensibiliser les actrices et acteurs dediversmilieuxetàsoutenirdeschangementsdurablesafinderéduirela pollution urbaine.
Keywords: 2000 à aujourd'hui; afrique; afrique de l'ouest; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques

Conciliation vie familiale et vie professionnelle par les femmes travaillant dans le secteur public de la santé à Lomé : quelles stratégies d’adaptation ? - Bilampoa, Gnoumou Thiombiano; Sitsopé, Toudeka Ayawavi; David, Jean Simon (Interventions Économiques, 2021)
Cet article cerne les difficultés, les défis et les stratégies mises en œuvre par les femmes soignantes à Lomé (Togo) dans la conciliation travail-famille. Les données qualitatives ont été collectées auprès de femmes soignantes dans deux formations sanitaires publiques, de leur conjoint et de leurs collègues hommes. Les résultats montrent que les normes et les pratiques culturelles ont confiné les hommes et les femmes dans leurs rôles respectifs selon la division sexuelle du travail. Ainsi, exercer des tâches domestiques est considéré comme un devoir pour les femmes, mais une transgression des normes sociales pour les hommes. Les exigences et les conditions de la profession médicale et l’insuffisance de personnels de santé rendent difficile la conciliation travail-famille pour les femmes. Pour concilier leur vie familiale et professionnelle, les femmes soignantes mettent en œuvre plusieurs stratégies d’adaptation : recours à l’aide parentale, emploi de domestiques et de répétiteurs scolaires, acquisition d’appareils électroménagers.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; care; conciliation famille-travail; famille; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; togo; travail; travail domestique; travail du care

Hidden in plain sight: Gender analysis of the environmental and social impact assessment of the East African crude oil pipeline - Hill, Christina; Namara, Charité; Orcaya, Jane; Bogrand, André; Sellwood, Scott A. (Impact Assessment and Project Appraisal, 2021)
Large-scale mining, oil, and gas projects can have a profound and negative affect on women’s rights and gender equality. Adverse impacts include the disruption of family and social life; the increased risks to health and safety, especially in terms of domestic and sexual violence; environmental degradation; as well as changing access to and control over land and livelihoods. These adverse impacts fall most heavily on women. This case study focused on the East African Crude Oil Pipeline (EACOP). It shows that conventional environmental and social impact assessment (ESIA) processes may not identify all potential adverse impacts on women, and can fail to analyse the implications of potential impacts on gender norms and gender power relations, leading to a downplaying of the significance of these impacts. The implications for women and girls’ health and safety resulting from the in-migration of large numbers of mostly men seeking project employment and other opportunities and increases in women’s unpaid care work are two potential adverse impacts the EACOP ESIA failed to identify. Strengthening gender analysis within the current suite of impact assessment tools and methodologies, particularly for extractive industries projects, is therefore urgently needed. © 2021 IAIA.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; environnement; extractivisme; industrie pétrolière; ouganda; patriarcat; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; violences

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences